ERP and Business Process Improvement, A Case Study in Manufacturing Industry - Periainen, Irina (2024)
Periainen, Irina ERP and Business Process Improvement, A Case Study in Manufacturing Industry Jyväskylä: University of Jyväskylä, 2024, 66 pp. Major subject, type of the publication (Information Systems, Master’s Thesis) Supervisor: Pulkkinen, Mirja